PERSONAL INCOME TAX PARADOX: ANALYSIS OF REVENUE DETERMINANTS IN ASEAN COUNTRIES 2010-2023 - Febriyanti, Afiqoh Zulfah; Nugroho, Rahadi (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2026)
This study investigates the determinants of personal income tax (PIT) revenue in ASEAN countries, addressing the paradox of stagnant tax ratios despite sustained economic growth. Although ASEAN economies have developed rapidly, PIT contributes only 12.7% of total tax revenue, substantially below the OECD average of 23.7%. This study analyzes the effects of GDP per capita, industrial sector development, unemployment rate, and statutory tax rates on PIT revenue across eight ASEAN countries during 2010–2023. Using panel data from 112 observations, a random effects regression model is employed to capture cross-country heterogeneity. Unlike prior studies that emphasize aggregate tax performance, this research specifically focuses on PIT and integrates macroeconomic indicators with fiscal policy instruments within the contemporary ASEAN context. The findings show that GDP per capita and industrial sector expansion positively affect PIT revenue, reflecting the role of income growth and structural transformation toward formal employment. Conversely, higher unemployment rates significantly reduce tax collection capacity. Tax rates exhibit a positive relationship with revenue, although their effectiveness depends on the design and progressivity of the tax system. The results reveal a structural paradox: while PIT revenue increases, overall tax ratios remain stagnant, indicating inefficiencies in tax bases, compliance, and institutional capacity. Policy implications include optimizing income thresholds relative to GDP, promoting formal sector expansion, and implementing comprehensive tax reforms that integrate macroeconomic structure with fiscal design.